Proceedings of the 4th Symposium on Applied Perception in Graphics and Visualization 2007
DOI: 10.1145/1272582.1272605
|View full text |Cite
|
Sign up to set email alerts
|

Psychophysics for perception of (in)determinate art

Abstract: The question of how humans perceive art and how the sensory percept is endowed with aesthetics by the human brain has continued to fascinate psychologists and artists alike. It seems, for example, rather easy for us to classify a work of art as either "abstract" or "representational". The artist Robert Pepperell recently has produced a series of paintings that seek to defy this classification: his goal was to convey "indeterminancy" in these paintings -scenes that at first glance look like they contain an obje… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 9 publications
0
8
0
Order By: Relevance
“…For example, the spontaneous gaze behavior in viewing artworks seems to follow a “coarse-to-fine” strategy where an initial global sweep of the image is followed by a later period of visual scrutiny of finer local details (Locher et al, 2007 ). Furthermore, the points of high salience computed in terms of local feature differences in luminance, color and orientation were found to drive eye fixations in viewing abstract and representational artworks (Wallraven et al, 2007 ; DiPaola et al, 2010 ; Foulsham and Kingstone, 2010 ; Fuchs et al, 2011 ). Based on these investigations, how the eye scans across Pollock's patterns, which lack obvious salient features and which scale across multiple sizes, is of obvious interest.…”
Section: How Does the Eye Search Through The Visual Complexity Of Polmentioning
confidence: 99%
“…For example, the spontaneous gaze behavior in viewing artworks seems to follow a “coarse-to-fine” strategy where an initial global sweep of the image is followed by a later period of visual scrutiny of finer local details (Locher et al, 2007 ). Furthermore, the points of high salience computed in terms of local feature differences in luminance, color and orientation were found to drive eye fixations in viewing abstract and representational artworks (Wallraven et al, 2007 ; DiPaola et al, 2010 ; Foulsham and Kingstone, 2010 ; Fuchs et al, 2011 ). Based on these investigations, how the eye scans across Pollock's patterns, which lack obvious salient features and which scale across multiple sizes, is of obvious interest.…”
Section: How Does the Eye Search Through The Visual Complexity Of Polmentioning
confidence: 99%
“…We note that one group performed experiments using rapid categorization that explored the processing of abstraction in painting (Wallraven et al, 2007). These experiments showed that the "indeterminate" artwork of Robert Pepperell showed significant differences in terms of reaction time for categorization compared to more representational artworks.…”
Section: Discussionmentioning
confidence: 99%
“…My ongoing research into the scientific background relating to visual indeterminacy led me to collaborate with two groups of vision scientists, one at Max Planck Institute for Biological Cybernetics 36 and the other at the University of Zürich. 5 The purpose was to subject the viewers of my paintings to a series of psychophysical, behavioural and neurobiological tests in order to investigate their responses to visually indeterminate images.…”
Section: Visual Indeterminacymentioning
confidence: 99%